1996
DOI: 10.1007/bf00262821
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physical exercise on adoptive experimental auto-immune encephalomyelitis in rats

Abstract: The aim of the study was to determine whether different programmes of exercise influence adoptive monophasic experimental auto-immune encephalomyelitis (adoptive EAE), a paralytic disease mediated by T-cells. Adoptive EAE was induced by the transfer of activated encephalitogenic T-lymphocytes into syngeneic recipients (Lewis rats, n = 85) and its development was followed by two independent observers. The results showed that 2 days of severe exercise (250 and 300 min) performed after the adoptive transfer of EA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 23 publications
3
34
0
Order By: Relevance
“…Studies in experimental autoimmune encephalomyelitis (EAE), an animal model of MS, have shown that exercise during the induction phase of the disease does not aggravate the course of disease [10]. None of the clinical MS studies mentioned above reported enhancement of the inflammatory activity or exercise-induced exacerbations (for review, see Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in experimental autoimmune encephalomyelitis (EAE), an animal model of MS, have shown that exercise during the induction phase of the disease does not aggravate the course of disease [10]. None of the clinical MS studies mentioned above reported enhancement of the inflammatory activity or exercise-induced exacerbations (for review, see Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors also reported delayed onset of clinical EAE signs following voluntary wheel running in chronic EAE mice [5] and treadmill running in rats [3,4]. It is difficult to compare different studies due to application of different exercise intensities (lower versus higher intensities) or due to the use of voluntary exercise versus quantified training load and intensity.…”
Section: Discussionmentioning
confidence: 99%
“…So far, research investigating the impact of EAE and/or physical exercise during EAE on muscle contractile properties and EAE progression is scarce, conflicting but also promising [2][3][4][5]. De Haan and co-workers explored the impact of EAE on muscle contractile properties.…”
Section: Introductionmentioning
confidence: 99%
“…While there is no cure for MS, exercise appears to be beneficial at multiple levels, and it may have an important role to play in delaying negative symptoms of the disease. For example, animal research has suggested that exercise might provide an antiinflammatory effect, potentially slowing the disease process [21]. Extending this research to human participants is an important next step in MS research.…”
Section: Future Directionsmentioning
confidence: 99%